Bisdemethoxycurcumin promotes apoptosis in human platelets via activation of ERK signaling pathway. (March 2020) - Paul, Manoj; Manikanta, Kurnegala; Hemshekhar, Mahadevappa; Sundaram, Mahalingam S.; Naveen, Shivanna; Ramesh, Thimmasandra Narayan; Kemparaju, Kempaiah; Girish, Kesturu S.
Abstract: Curcumin, a major bioactive component of turmeric ( Curcuma longa ), is known for its multiple health benefits. Curcumin as such is a mixture of its analogs: bisdemethoxycurcumin (BDMC)-3%, and demethoxycurcumin (DMC)-17%. Although the effect of curcumin on platelets is documented, the effect of BDMC and DMC on platelets is less studied. Considering the indispensable role played by platelets in hemostasis, thrombosis, inflammation, and immunity, the present study evaluates the effect of curcumin, DMC and BDMC on platelet apoptosis. The components of curcumin were purified by silica-gel column chromatography. The purity and mass analysis of the purified curcuminoids was determined by RP-HPLC and LC-MS respectively. When analyzed for platelet apoptotic markers, only BDMC demonstrated increased incidence of platelet apoptotic markers including increase in intracellular Ca 2+, decrease in ∆ψ m, alteration in BCl-2 family proteins, the release of cytochrome c, caspase activation, and PS externalization via activation of ERK activation. ERK inhibitor PD98059 significantly alleviated BDMC induced decrease in ∆ψ m, alteration in BCl-2, caspase-8 activation and PS externalization. Our results demonstrate that curcumin, DMC and BDMC differentially act on platelet in inducing apoptosis and the study highlights that the toxicity associated with curcumin therapy might be attributed to BDMC in the mammalian system. Highlights: Bisdemethoxycurcumin (BDMC) was found to induce apoptosis in platelets. BDMC induced platelet apoptosis was mediated by ERK activation. The study highlights that platelets could undergo apoptosis via extrinsic pathway.